2017
DOI: 10.1055/s-0037-1598649
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Measurement of Inferior Turbinate in Asymptomatic Adult

Abstract: Introduction  The inferior turbinate (IT) is the most susceptible turbinate to enlargement causing nasal obstruction. The common belief ascribes most of the enlargement of the IT to mucosal elements. Objective  This study aimed to investigate the detailed computed tomography (CT) measurement of the IT in asymptomatic adult by determining the thickness of both the non-bony (mucosa) and bony parts and their relation to nasal air space in different related areas of the nose. Methods  We included in the study pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…In the current study the mean width of NHT and the mean width HT in patients with NSD was 7.27 ± 0.67 m and 10.46 ± 2.63 mm respectively. Similar measurements were presented in many CT studies from Egypt and Iraq [ 30 – 33 ].…”
Section: Discussionsupporting
confidence: 83%
“…In the current study the mean width of NHT and the mean width HT in patients with NSD was 7.27 ± 0.67 m and 10.46 ± 2.63 mm respectively. Similar measurements were presented in many CT studies from Egypt and Iraq [ 30 – 33 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, if a CT scan of the nose and paranasal sinuses has been obtained for other reasons, it may provide useful information, such as assessment of bony versus mucosal hypertrophy. 9 El-Anwar et al 10 provided normal CT parameters that we used as reference in our study; the results of post-operative CT scans were near the normal parameters of the normal inferior turbinate reported in that study. In addition, our study demonstrated that the nasal cavity distance (airway space) was wider than the normal parameters previously reported.…”
Section: Resultssupporting
confidence: 70%
“…The model simulated the nasal cavity, wherein the NPS has to be inserted to reach the nasopharynx, and was based on computed tomography measurements done on an asymptomatic adult‐sized nasal air space. [ 56 ] NPS designs with different shafts and different head volumes and the viscous behaviors of the artificial mucus both affected retention rates significantly. Due to the slight bend in the nasal pathway featured in the model, NSP with a rigid shaft design (designs V–VIII, X, and XIV) had a tendency to break while turning inside the 10 mL narrow‐mouth Erlenmeyer flask.…”
Section: Preclinical Swab Design Testingmentioning
confidence: 99%